2020
DOI: 10.1002/smll.201906076
|View full text |Cite
|
Sign up to set email alerts
|

Prelithiated V2C MXene: A High‐Performance Electrode for Hybrid Magnesium/Lithium‐Ion Batteries by Ion Cointercalation

Abstract: The pursuit of high reversible capacity and long cycle life for rechargeable batteries has gained extensive attention in recent years, and the development of applicable electrode materials is the key point. Herein, thanks to the preintercalation of lithium ions, a stable and highly conductive nanostructure of V2C MXene is successfully fabricated via a facile self‐discharge mechanism, which provides open spaces for rapid ion diffusion and guarantees fast electron transport. Taking the prelithiated V2C as electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(77 citation statements)
references
References 43 publications
3
74
0
Order By: Relevance
“…Transmission electron microscopy (TEM) analysis of exfoliated nanosheets ( Figure 1B) exhibits the as-prepared V 2 CT x nanosheets to be quite thin with ~50 to ~200 nm lateral range. The crystal structure was further confirmed by high-resolution TEM and selected area electron diffraction, exhibiting a set of clear lattice fringes with an inner plane spacing of 0.24 nm ( Figure 1C), corresponding to the (01 ̅ 10) plane of MXene V 2 C, Figure 1C, in good agreement with previous results [36,37]. Atomic force microscopy was employed to further investigate the as-synthesized MXene V 2 CT x nanosheets ( Figure 1D).…”
Section: Fabrication and Characterization Of Mxene (V Ct X )supporting
confidence: 86%
“…Transmission electron microscopy (TEM) analysis of exfoliated nanosheets ( Figure 1B) exhibits the as-prepared V 2 CT x nanosheets to be quite thin with ~50 to ~200 nm lateral range. The crystal structure was further confirmed by high-resolution TEM and selected area electron diffraction, exhibiting a set of clear lattice fringes with an inner plane spacing of 0.24 nm ( Figure 1C), corresponding to the (01 ̅ 10) plane of MXene V 2 C, Figure 1C, in good agreement with previous results [36,37]. Atomic force microscopy was employed to further investigate the as-synthesized MXene V 2 CT x nanosheets ( Figure 1D).…”
Section: Fabrication and Characterization Of Mxene (V Ct X )supporting
confidence: 86%
“…Mg 2+ or Mg-based complexes, are irreversibly intercalated or adsorbed on the surface of the V 2 O 5 nanobers. As it is reported that Mg 2+ can be intercalated but not de-intercalated, 8,12,28,29 we assume that Mg 2+ is the species which is irreversibly intercalated. To verify this, we analyzed the shi of the anodic peak current towards higher potentials with increasing the scan rate.…”
Section: Resultsmentioning
confidence: 99%
“…[ 52 ] In addition, MXene also possesses excellent performance in magnesium/lithium‐ion batteries (MLIBs), [ 53 ] for example, by Mg 2+ /Li + co‐intercalation, the prelithiated V 2 C MXene with a stable and highly conductive nanostructure possessed a high reversible capacity of up to 230.3 mA h g −1 at 0.02 A g −1 and a fascinating capacity retention of 82% over 480 cycles in MLIBs. [ 54 ] Considering the large variety of MXenes, these works indicate that much more cathode materials are potentially available for RMBs.…”
Section: Cathodesmentioning
confidence: 99%